Juntos mais desiguais: um desejo de "nação" paulista não-realizado - Magri, Mailce (2011)
Assuming that every nation is an imagined community concept created by Benedict Anderson in his book Imagined Communities I propose a discussion about the existence of different projects for the construction of a Brazilian nation, paying special attention to a "Sao Paulo state project". As guideline, I use the subaltern studies, which question the hegemonic centers' theoretical colonialism and the modernity dominant conceptions. This dissertation is based on the subaltern studies literature and on the selection of texts from the period chosen for this study: the years between 1870-1922. These analyses intend to show the existence of a "Sao Paulo project" for the nation, which demonstrates a "admiration" for the North- American racial segregation. This "admiration" was a common theme in many papers written after such project failed.